Education, Inclusion, Pluralism and United Nations Sustainable Development Goals : A Case Study of the Cultural Politics of Postcolonial Pakistan - Khan, Sher Rahmat (Educational Research E-Books Online, Collection 2025., 2025)
This book offers a compelling analysis of education's promise to achieve inclusive, pluralistic and sustainable societies. These globally shared challenges are examined through a detailed analysis of the cultural politics of education in postcolonial Pakistan. The analysis provides a window into the ways that the intergenerational traumas of colonialism, neocolonialism, globalisation and forms of extremism continue to present significant challenges for postcolonial Pakistan. Drawing on postcolonial theories and curriculum theory, the author develops a critical discourse analysis of the cultural politics that shapes education in Pakistan. The analysis identifies key elements of this cultural politics such as religious and cultural dynamics, geopolitical challenges, the need to promote unity and cohesion, employing history for nation-building, and gender relations, and the ways in which these elements intersect to shape the possibilities of delivering on the promise of inclusion, pluralism and sustainable development.